Assessment of genes LRP5, BVP4, TGF^l polymorphisms significance in postmenopausal osteoporosis - KA Myakotkin; M. Y. Krylov; A. Y. Kaseeva; K A Maslova; N. K. Toroptsova; O A Nikitinskaya; L J Benevolenskaya (Научно-практическая ревматология)
180 women with primary postmenopausal osteoporosis (OP) (mean age 67,5+7,8 years) were included. 118 postmenopausal women without osteoporosis and osteopenia (mean age 63,8±8,1 years) formed control group. Higher frequency of LRP5 gene CT genotype was revealed in pts with OP in comparison with control (OR=2,2; p=0,005). Tendency to increase of gene BMP4 AA genotype and gene TGFfi CC genotype was found in pts with OP in comparison with control. But the difference was not statistically significant. OP pts showed accumulation of CTCC (gene LRP5 and TGFfil combination) and CTAV (gene LRP5 and BMP4 combination) compounds increasing risk of the disease by a factor of 4 (p=0,0004) and 2,5 (p=0,035) respectively. Association was revealed between LRP5 and TGFfil (r=0,26; p=0,001), between polymorphisms of these genes and alkaline phosphatase level (r=0,22; p=0,004 and r=0,16; p=0,04 respectively), between gene BMP4 polymorphisms and serum osteoprotegerin concentration (r=0,2; p=0,0l6). Combined LRP5/TGF$1 genotype was associated with femur neck BMD (r=0,20; p=0,014) and LRP5/BMP4 - with trochanter BMD (r=0.16; p=0,055). Carriers of gene LRP5 CT genotype, gene TGFfil TT genotype and gene BMP4 W genotype had lower mean BMD values in femur neck and trochanter.